Effect of Tulsi (Ocimum sanctum) Leaf and Synbiotic Powder on Growth Performance, Nutrient Utilization, Carcass and Blood Biochemical Parameters in Broilers - Kohri, A.; Shende, K. A.; Dhuria, R. K.; Goklaney, D. (Indian Journal of Animal Nutrition, 2022)
A six-week feeding trial was followed by a metabolic trial using 120 broiler chicks (Cob-400) in a completely randomized block design to assess the effect of dietary supplementation with tulsi leaf and synbiotic powder as feed additives on growth performance of broilers. The four dietary treatments were designated as TC control group (basal diet), T1 supplemented with tulsi @ 0.5%, T2 supplemented with synbiotic @ 0.05%, T3 supplemented with tulsi @ 0.5% and synbiotic @ 0.05% of feed. Growth performance and carcass yields were significantly higher (P<0.01) in dietary treatment with supplementation of tulsi leaf and synbiotic as compared to control. Significantly higher body weight, weight gain, daily weight gain, protein efficiency ratio and performance index were observed in the T3 group supplemented with a combination of tulsi and synbiotic @ 0.5 percent and 0.05 percent, respectively. Similarly, dietary supplementation of tulsi leaf and synbiotic in combination significantly reduced serum triglyceride and cholesterol level. Whereas, dietary inclusion of tulsi leaf alone and in combination with synbiotic reduced feed intake and feed conversion ratio. However, dry matter digestibility, nitrogen balance, eviscerated weight, heart, liver, gizzardweights, total protein, albumin, globulin, haemoglobin and packed cell volume did not differ in treatment groups. The mortality rate was found to be lower in the treatment groups when compared to the control group. Based on the findings of this study, it is concluded that supplementing tulsi leaf at 0.5 percent with synbiotic powder at 0.05 percent improved the growth performance, nutrient utilization, carcass traits and blood haemato-biochemical parameters of broiler chicks without any negative effects.